IMPROVING THE METHODOLOGY OF STUDENTS' ARTISTIC-PICTURE THINKING DEVELOPMENT IN THE TEACHING OF PAINTING SCIENCE - Ibatova Nigora Istamovna (Scholars Digest Publishing, 2024)
The development of artistic-picture thinking is essential in the education of students studying painting science. This article explores various methodologies to enhance artistic-picture thinking, emphasizing its importance in fostering creativity, critical thinking, and emotional expression. By integrating art theory with practical application, encouraging observational drawing, promoting visual analysis and critique, incorporating art history, fostering imagination, utilizing technology, and facilitating collaborative projects, educators can significantly enhance students' artistic capabilities. The article also discusses successful case studies and the challenges educators may face in implementing these methodologies. Ultimately, this holistic approach to art education aims to cultivate well-rounded individuals capable of making meaningful contributions to society.
Keywords: Artistic-picture thinking, painting science education, art theory, observational drawing, visual analysis, art history, creativity, critical thinking, digital art.